The Aims of Big History. Issue 7 (July 2015) - Turnbull, Paul
Abstract Big History studies the history of humankind within the historical time scales of geological and biological history. It does so to understand how powerful forces and factors at work on these large time‐scales have shaped our history. It focuses particularly on how societies throughout the world have responded to major environmental, economic and social changes. David Christian and other practitioners of Big History hold that although we have become less constrained since the end of the Palaeolithic era by our biology, our life‐ways, forms of social organization and culture have continued to be influenced by our biology and by the play of large‐scale and long‐term natural forces, notably our planet's weather and ecological systems. In this article, I discuss Big History's particular focus on our development of social complexity and technological innovations in response to our energy needs. I also consider Big History's emphasis on our evolution of symbolic communication, drawing attention to the disinclination of practitioners of Big History to adopt rigorously Darwinian interpretations of our cultural and social evolution. The article concludes by way of brief comments on David Christian's championing of Big History as a return to universal history and some personal brief observations on teaching Big History.